2019
DOI: 10.3390/ijerph16152636
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Geogenic Particulate Matter to Lung Disease in Indigenous Children

Abstract: Indigenous children have much higher rates of ear and lung disease than non-Indigenous children, which may be related to exposure to high levels of geogenic (earth-derived) particulate matter (PM). The aim of this study was to assess the relationship between dust levels and health in Indigenous children in Western Australia (W.A.). Data were from a population-based sample of 1077 Indigenous children living in 66 remote communities of W.A. (>2,000,000 km2), with information on health outcomes derived from ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Remote Australian Aboriginal communities are exposed to high levels of inorganic particulate matter (Shepherd et al 2019), dominated by silica and iron oxides (Zosky et al 2014b), and have a disproportionate burden of chronic respiratory infections . The present study aimed to identify whether silica or iron oxide PM can directly modify the growth of NTHi as one of the dominant forms of pathogenic respiratory bacteria in these communities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Remote Australian Aboriginal communities are exposed to high levels of inorganic particulate matter (Shepherd et al 2019), dominated by silica and iron oxides (Zosky et al 2014b), and have a disproportionate burden of chronic respiratory infections . The present study aimed to identify whether silica or iron oxide PM can directly modify the growth of NTHi as one of the dominant forms of pathogenic respiratory bacteria in these communities.…”
Section: Discussionmentioning
confidence: 99%
“…While there are a range of factors associated with social disadvantage that may be contributing to this unacceptably high burden of disease (Australian Bureau of Statistics 2017; Australian Institute of Health and Welfare 2016; Melody et al 2016;, emerging evidence suggests environmental factors also contribute (Clifford et al 2015). For example, geogenic (earth-derived) particulates are abundant in remote Aboriginal communities (Clifford et al 2015;Melody et al 2016) and are correlated with the severity of lower respiratory tract infections in these communities (Shepherd et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…These communities also have a disproportionate burden of chronic respiratory infections resulting in bronchiectasis (Blackall et al, 2018). The present study aimed to investigate the effect of iron oxide, with or without prior LPS exposure, on inflammation in macrophages and on bacterial phagocytosis as potential contributors to the detrimental health outcomes observed in individuals exposed to iron-laden geogenic PM [ 9 ]. Iron oxide particles clearly modified the effect of LPS on the macrophages, which varied between particle types and across cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of bronchiectasis is almost three times higher in Australian Aboriginals living in rural communities [ 2 ] and these communities have among the highest prevalence of bronchiectasis in children globally [ 3 ]. While these communities often have comparatively higher rates of smoking and restricted access to medical services [ 4 , 5 , 6 ], other environmental factors may be contributing to this disease disparity [ 7 , 8 , 9 ]. Previous studies have suggested that exposure to air pollution is associated with increased bronchiectasis exacerbations and mortality [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…While the extremes of outdoor dust exposures, labeled dust events or desert dust storms, are well-documented causes of increased hospital admissions and even mortality for asthma, COPD, and cardiovascular disease in people [ 3 ] and occupational exposure to silicates, such as seen in talc workers [ 4 ] is known to cause pneumoconiosis and silicosis in humans, there is also a considerable but less extreme quotidian outdoor exposure to inorganic particulates, known as ‘aolian’, geogenic, or desert dust of crustal origin, in arid parts of the world, including the West coast of the USA [ 5 ]. Higher exposure to geogenic (earth-derived) dust in arid regions is a strong risk factor for both allergic and infectious respiratory illness in indigenous children in Australia [ 6 , 7 ], and farmers exposed to high levels of geogenic dust in arid regions also have an increased risk of both infectious and non-infectious disease [ 1 ]. Moreover, there has been recognition and documentation that geogenic dust causes a disproportionate burden of respiratory disease in people in disadvantaged areas of the world [ 6 ].…”
Section: Introductionmentioning
confidence: 99%